Progress in Borneol Intervention for Ischemic Stroke: A Systematic Review - Li, Yong; Ren, Mihong; Wang, Jiajun; Ma, Rong; Chen, Hai; Xie, Qian; Li, Hongyan; Li, Jinxiu; Wang, Jian (Frontiers in Pharmacology, 2021)
Background: Borneol is a terpene and bicyclic organic compound that can be extracted from plants or chemically synthesized. It is an important component of proprietary Chinese medicine and is an important component in stroke medications; its neuroprotective effects have been confirmed in many experiments. This study aimed to systematically examine the neuroprotective effects of borneol in the cascade reaction of experimental ischemic stroke at different periods. Methods:Articles on animal experiments and cell-based research on the actions of borneol against ischemic stroke in the past 20 years were collected from Google Scholar, Web of Science, PubMed, ScienceDirect, China National Knowledge Infrastructure, and other biomedical databases. After sorting the articles, we focused on the neuroprotective effects and mechanism of action of borneol at different stages of cerebral ischemia. Results:Borneol is effective in the prevention and treatment of nerve injury in ischemic stroke. Its mechanisms of action include improvement of cerebral blood flow, inhibition of excitatory amino acid toxicity, blocking of Ca2+ overload, and resistance to reactive oxygen species injury in the acute ischemic stage. In the subacute ischemic stage, borneol may antagonize blood–brain barrier injury, intervene in inflammatory reactions, and prevent neuron death. In the late ischemic stage, borneol promotes neurogenesis and angiogenesis in the treatment of ischemic stroke. Conclusions:Borneol prevents neuronal injury after cerebral ischemia via different mechanisms of action and can mobilize endogenous nutritional factors to hasten repair and regeneration. Because the therapeutic effects of borneol are mediated by various therapeutic factors, deficiency caused by a single-target drug is avoided. Borneol can promote the passage of other drugs through the blood–brain barrier and enhance the therapeutic effect of these drugs.